The Role of Government Environmental Policy and Industrial Factors on Corporate Financial Performance Mediated by Environmental Accounting Management - Rumasukun, Mohammad Ridwan; Noch, Muhammad Yamin (International Journal of Energy Economics and Policy, 2026)
This study aims to investigate the interrelationships among Government Environmental Policy (GEP), Industry Factors, and Environmental Accounting Management (EAM) with Corporate Financial Performance (CFP), examining both direct and indirect effects through mediating variables. A quantitative methodology is employed, wherein GEP, Industry Factors, and EAM are assessed using questionnaires, while CFP data is sourced from the company’s financial reports over the past five years. To harmonize the scale between quantitative and qualitative data, computer analysis and interval range methods are applied to financial ratio values. Data analysis is conducted using Structural Equation Modeling (SEM) via Smart PLS software. The results of the study reveal that the relationships between GEP, Industry Factors, and EAM with CFP, whether directly or through mediating variables, are positive and significant. The findings of this research support the hypothesis that environmental practices influenced by government environmental policies and industrial factors affect corporate financial performance. This study makes both theoretical and practical contributions to the understanding of the connections between environmental policies, industrial practices, environmental accounting management, and corporate financial performance. It is essential to note that this study has significant implications for the development of more effective environmental policies and sustainable corporate management strategies. These conclusions highlight the importance of considering environmental factors in business decision-making and underscore the need to integrate environmental strategies into long-term business plans.